Strategi Manajemen Operasional SDM dalam Meningkatkan Kinerja Karyawan: Penelitian - Retno Ayu Puspita S; Muh. Ferils (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Amid intense business competition, human resources (HR) have become a strategic asset for organizational success. Beyond technology and capital, companies must manage HR effectively to achieve their goals. Operational HR management plays a crucial role in creating efficient and sustainable work systems. This study uses a literature review method by analyzing books, academic articles, online sources, and relevant publications. The findings show that effective HR management includes competency-based recruitment, structured training, KPI-based performance management, compensation and reward systems, and coaching and mentoring. These practices form a high-performance work system that enhances employee ability, motivation, and opportunities. Clear expectations, real-time feedback, and appropriate recognition boost productivity, adaptability, and loyalty. Support from top management and active involvement of line managers ensure HR strategies align with business goals and positively impact company performance.